2005
DOI: 10.1007/s00248-003-2030-7
|View full text |Cite
|
Sign up to set email alerts
|

Limnothrix redekei (Van Goor) Meffert (Cyanobacteria) Strains from Lake Kastoria, Greece Form a Separate Phylogenetic Group

Abstract: Three strains of Limnothrix (Cyanobacteria) isolated from Lake Kastoria, Greece, were characterized based on their morphological features and 16S rRNA gene sequences. The Limnothrix isolates 007a, 165a, and 165c can morphologically be assigned to Limnothrix redekei (Van Goor) Meffert. The 16S rRNA gene of the Limnothrix strains showed a 99% similarity to the 16S rRNA gene of Planktothrix sp. FP1. Limnothrix redekei strains 165a, 165c, 007a and Planktothrix sp. FP1 formed a separate cluster in the cyanobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 25 publications
5
74
0
2
Order By: Relevance
“…Diversity of Pseudanabaena populations SG Acinas et al strains isolated from Lake Kastoria (Greece), has also been observed (Gkelis et al, 2005;Willame et al, 2006). On the basis of partial sequencing of the 16-and 23S rRNA genes, all Pseudanabaena strains are isolated in this study cluster with the Pseudanabaena/Limnothrix group.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Diversity of Pseudanabaena populations SG Acinas et al strains isolated from Lake Kastoria (Greece), has also been observed (Gkelis et al, 2005;Willame et al, 2006). On the basis of partial sequencing of the 16-and 23S rRNA genes, all Pseudanabaena strains are isolated in this study cluster with the Pseudanabaena/Limnothrix group.…”
Section: Discussionsupporting
confidence: 60%
“…This cluster is commonly referred to as the Pseudanabaena/Limnothrix group (Gkelis et al, 2005;Willame et al, 2006). This group also comprised several environmental sequences as well as other isolates including the type strain Pseudanabaena PCC7408, strains belonging to L. redekei (Van Goor, Meffert) (Limnothrix sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…45 More recently, Gkelis et al presented evidence that a Limnothrix strain was previously misidentified as a Planktothrix strain. 46 DNA-analyses should therefore be used as an important identification factor for culture collections, similarly to what has recently been done 47 on a small scale with a green algae collection from Germany.…”
Section: 10 Synechocystis Sp Pcc 6803mentioning
confidence: 99%